Work Motivation and Satisfaction and Its Impact on Lecturer Performance - Hanafiah Hanafiah; Nasrun Nasrun; Restu Restu (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The performance of lecturers in a university is measured through Tri Darma namely education, research, and community service. This research is a quantitative study using regression analysis. The research sample was 186 lecturers at Samudra Langsa University determined using tablesKrejcie. The questionnaire is a data collection tool used in this study. Data analysis using EViews.10 The results showed that partially; (1) work motivation (X1) influences lecturer performance; (2) job satisfaction has an effect onlecturer performance; and simultaneously obtained that; (3) work motivation and job satisfaction have a positive and significant effect on lecturer performance. The magnitude of the contribution of independent variables to the dependent variable is 27.86% and the rest 72.14% is influenced by variables not observed in this study. So it can be concluded thatfor one of the efforts that can be done to improve the performance of lecturers at Samudra Langsa University is to increase the motivation and job satisfaction of lecturers.